Improving competitiveness through financial solutions: a study of Vietnam posts and telecommunications (vnpt) - Nguyễn, Đức Anh (2020)
Basic theory on firm’s competitiveness and the role of finance in improving competitiveness of enterprises: Competitiveness is a vital characteristic of the market economy. There are broad and varied definitions of competition and competitiveness concept based on different schools of thought and the level of analysis. Finance plays an important role in policy and decision making in enterprises which influencing directly on their competitiveness and profits. Financial factors include taxation, state investments on supporting industries, enterprises’ financing and budgeting, enterprises’ distribution policies. 2. Analysis of VNPT competitiveness and its contemporary financial solutions for improving competitiveness during 2014 – 2018: Overall, although VNPT is still one of the biggest posts and telecommunications in Vietnam, but their position is no longer dominant. To enhance competitiveness, VNPT has focused on three groups of financial solutions, including: Investment restructuring, market expanding, comprehensive domestic and international cooperation.